EN FACE OPTICAL COHERENCE TOMOGRAPHY AND OPTICAL COHERENCE TOMOGRAPHY ANGIOGRAPHY OF MULTIPLE EVANESCENT WHITE DOT SYNDROME: New Insights Into Pathogenesis. (December 2016) - Pichi, Francesco; Srvivastava, Sunil K.; Chexal, Saradha; Lembo, Andrea; Lima, Luiz H.; Neri, Piergiorgio; Saitta, Andrea; Chhablani, Jay; Albini, Thomas A.; Nucci, Paolo; Freund, K. Bailey; Chung, Hyewon; et al.
Abstract : Purpose: To localize the various levels of abnormalities in multiple evanescent white dot syndrome by comparing "en face" optical coherence tomography (OCT) and OCT angiography with various conventional imaging modalities. Methods: In this retrospective case series, multimodal imaging was performed in 9 retinal centers on 36 patients with multiple evanescent white dot syndrome and included widefield fundus autofluorescence (FAF), fluorescein angiography (FA), and indocyanine green angiography, and B-scan and "en face" C-scan enhanced depth imaging and spectral domain OCT. Optical coherence tomography angiography was also performed at the level of the superficial and deep retinal capillary plexus and choroid. Results: Multiple evanescent white dot syndrome lesions were more numerous and more easily detectable with FA and FAF. Two types of lesions were identified with FAF, FA, and indocyanine green angiography: larger widely scattered "spots" (approximately 200 μ in diameter) that were hyperfluorescent with FA, hyperautofluorescent with FAF, and hyporeflective in indocyanine green angiography, representing abnormalities primarily at the retinal pigment epithelium/photoreceptor junction; and punctate "dots" (less than 100 μ in diameter) that were hyperfluorescent with FA, hyperautofluorescent, or isoautofluorescent with FAF, and hypofluorescent with indocyanine green angiography and that localized to the outer nuclear layer. These lesions colocalized with "en face" OCT. The larger confluent "spots" were hyporeflective and colocalized to the level of the ellipsoid zone, whereas smaller hyperreflective "dots" colocalized to the outer nuclear layer. The location of the "dots" in the outer nuclear layer was further confirmed by structural spectral domain optical coherence tomography which showed coalescence of the dots into hyperreflective lines extending from the external limiting membrane to the outer plexiform layer in certain cases. Optical coherence tomography angiography analysis of the retinal microvasculature and choriocapillaris and choroid were entirely unremarkable in 100% of our patients. Conclusion: By combining multimodal imaging, the authors propose that multiple evanescent white dot syndrome is primarily the result of inflammation at the outer photoreceptor level leading to a "photoreceptoritis" and causing loss of the inner and outer segments. Its evanescent nature suggests that the photoreceptor cell bodies remain intact ensuring complete recovery of the photoreceptor inner and outer segments in most cases, compatible with the clinical course of spontaneous resolution of white spots and dots. Abstract : By combining multimodal imaging, the authors propose that multiple evanescent white dot syndrome is primarily the result of inflammation at the outer photoreceptor level leading to a "photoreceptoritis" and causing loss of the inner and outer segments. Its evanescent nature suggests that the photoreceptor cell bodies remain intact ensuring complete recovery of the photoreceptor inner and outer segments in most cases, compatible with the clinical course of spontaneous resolution of white spots and dots.